An Emerging Model for Virtual International Academic Conference in Architecture, Engineering, and Construction - Fang, Yanqing; Daniel, Emmanuel Itodo (Frontiers in Built Environment, 2021)
Academic conferences are very important to industrial development and academic scholars. However, the coronavirus disease 2019 pandemic has led to the cancellation of many international conferences; thus, virtual conferences have received a great deal of attention. Their expanding role has created an urgent need to explore the best approaches for successful execution. However, there is limited empirical evidence on the organization of these conferences. This study aims to offer a comprehensive analysis of the key success factors through a case study of the International Group for Lean Construction’s first virtual conference. The results revealed the influence of multiple factors. In addition, a successful model for an international virtual academic conference is proposed. The model contributes to the knowledge of sustainable development in engineering management and architecture, engineering, and construction practice.